Fueling Work Engagement: The Role of Sleep, Health, and Overtime - Schleupner, Ricarda; Kühnel, Jana (Frontiers in Public Health, 2021)
With the current study, we investigate mechanisms linking sleep quality with work engagement. Work engagement is an affective-motivational state of feeling vigorous, absorbed, and dedicated while working. Drawing from both the effort-recovery model and the job demands-resources framework, we hypothesize that sleep quality should be positively related to work engagement via the replenishment of personal resources that become apparent in mental health and physical health. Because personal resources should gain salience especially in the face of job demands, we hypothesize that overtime as an indicator for job demands should strengthen the positive relationship between mental health and work engagement. We gathered data from 152 employees from diverse industries via an online survey. Results showed that sleep quality was positively related to work engagement (r = .20, p < .05), and that mental health mediated this relationship (indirect effect: β = .23, lower limit confidence interval = .13, upper limit confidence interval = .34). However, physical health did not serve as a mediator. Overtime turned out to be significantly and positively related to work engagement (r = .22, p < .01), replicating previous findings, but did not significantly interact with mental health or physical health in predicting work engagement. Overall, the study highlights the significance of sleep quality for employees’ mental health and work engagement.